The influence of e-commerce business developments and technology-based accounting information systems on the need for e-commerce audit services - Nur Hayya Sophia (Institute of Accounting Research and Novation (IARN), 2023)
This study examines the effect of e-commerce business development and the development of technology-based accounting information systems on the need for e-commerce audit services. Respondents in this study were auditors who worked at Public Accounting Firms in Jakarta. The number of auditors who became the sample of this study were 135 auditors from 13 public accounting firms. The sample determination method used in this study was purposive sampling, while the data processing method used by the researcher was multiple regression analysis. The results of this study indicate that the development of e-commerce business and the development of technology-based accounting information systems simultaneously and significantly influence the need for e-commerce audit services.